(untitled) (Fiep Bulletin - online, 2014)
The thesis deals with monitoring of eating habits, fluid intake and physical activity of children of the 1st and 2nd stage of elementary schools in Broumov region. The research was conducted at 203 children from 2nd stage of elementary school. 101 pupils were from 5th grade, 102 pupils were from 9th grade. The information was obtained by anonymous questionnaire. It was found that most pupils, who have breakfast, snacks (morning and afternoon snacks) and dinner regularly are from the 5th grade. Their breakfast and snack are prepared by parents mostly, the lunch is consumed in the school cafeteria and they have dinner at home with their family. Fluid intake is determined by the age of pupils. Only 30 % of pupils of the 5th grade have recommended fluid intake (1.5 – 2 l). The pupil of 9th grade should drink 2 – 2.5 l of fluids a day. It was found that this recommendation is fulfil only by 23 % of pupils of 9th grade. It was found that the choice of fluids is determined by gender: girls drink more adequate fluids like water, juice, sugar free mineral water and tea. Boys prefer mineral water with sugar. Physical activity (except mandatory PE lessons at school) is performed mostly every day. From the research it is obvious that the physical activity is determined by age, because 44 % of pupils from the 5th grade have some physical activity every day, but from the 9th grade it is only 32 % of pupils. The most popular sports are ball games for boys and riding a bike for girls.